2016
DOI: 10.2147/cia.s103845
|View full text |Cite
|
Sign up to set email alerts
|

Assessment risk of osteoporosis in Chinese people: relationship among body mass index, serum lipid profiles, blood glucose, and bone mineral density

Abstract: ObjectiveThe aim of our study was to investigate the relationship among age, sex, body mass index (BMI), serum lipid profiles, blood glucose (BG), and bone mineral density (BMD), making an assessment of the risk of osteoporosis.Materials and methodsA total of 1,035 male and 3,953 female healthy volunteers (aged 41–95 years) were recruited by an open invitation. The basic information, including age, sex, height, weight, waistline, hipline, menstrual cycle, and medical history, were collected by a questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…The difference in BMD distribution between genders may be explained by the differences in endocrine and paracrine factors, and the rapid decrease of sex steroid levels in postmenopausal women aggravates the bone loss. 17 In addition, we found that the level of Apelin-13 was negatively related to age, demonstrating the risk of osteoporosis may be added with age, this conclusion was consistent with previous studies. 17 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The difference in BMD distribution between genders may be explained by the differences in endocrine and paracrine factors, and the rapid decrease of sex steroid levels in postmenopausal women aggravates the bone loss. 17 In addition, we found that the level of Apelin-13 was negatively related to age, demonstrating the risk of osteoporosis may be added with age, this conclusion was consistent with previous studies. 17 …”
Section: Discussionsupporting
confidence: 92%
“… 17 In addition, we found that the level of Apelin-13 was negatively related to age, demonstrating the risk of osteoporosis may be added with age, this conclusion was consistent with previous studies. 17 …”
Section: Discussionsupporting
confidence: 92%
“…Aging is one of the most important factors affecting bone mineral density (BMD), with certain underlying influential factors 1–3. However, many studies have been mainly focused on women concerning postmenopausal osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…This was a retrospective study of patients with RA, osteoporosis, and genu valgus treated using TKA at the Orthopedics Department of the Fourth A liated Hospital of Harbin Medical University between May 2016 and May 2019. This work has been carried out in accordance with the Declaration of Helsinki The inclusion criteria were: 1) preoperative femorotibial angle of 18°-27°; 2) rst-ever TKA; 3) TKA through the medial parapatellar approach; 4) severe osteoporosis, de ned as mean bone mineral density (BMD) Tvalue measured by dual-energy X-ray of -3.7 ± 0.6 [11]; and 5) follow-up of at least 1 year. The exclusion criteria were: 1) femorotibial angle > 27°; 2) received revision surgery; 3) TKA through the lateral parapatellar approach; 4) dual-energy X-ray absorptiometry (DEXA) showed that the T value of BMD >-3; and 5) poor compliance to follow-up.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…DEXA (Lunar DPX-NT; GE, Boston, Massachusetts, USA) was used to measure the bone mineral density (BMD) of the lumbar vertebral body, bilateral femoral necks, Ward's trigonum, and greater trochanter of all the patients on the anteroposterior images. All patients had to meet the diagnostic criteria of osteoporosis, as in the Suggested Diagnostic Criteria of Osteoporosis in Chinese People (2nd edition) issued in 2000 [11].…”
Section: Data Collectionmentioning
confidence: 99%